Effects of trigonella foenum graecumn (fenugreek) seeds aqueous extract on fertility of female rats - Mohamed Bakrim, Norbaiyah; Allow, Ahmed Kaid Naji; Al-Ani, Imad Matloub Dally; Mohd Hassan, Norazian (2018)
Despite a variety of contemporary methods for contraception, some women still rely on herbal plants as anti-fertility agents based on its common use for many years, passed down from generation to generation. One of these herbal plants is Trigonella foenum-graecum (fenugreek). The presence of saponin in fenugreek seeds is believed to be the active compound responsible for fenugreek anti-fertility property. The purpose of this study was to evaluate the effects of fenugreek seeds aqueous (FSA) extract on fertility of female rats by assessing estrous cycles, determining serum reproductive hormone concentrations and observing their ovarian tissue histology, as well as determining the reversibility of these effects once the treatment was withdrawn. Thirty two 8-week-old Sprague Dawley female rats with normal estrous cycle were divided into four groups (A, B, C and D). Animals in Group A (control group) were treated with distilled water as vehicle. Groups B and C (treatment group) were administered orally with 250 and 500 mg/kg body weight of FSA extract respectively for 15 days. Daily vaginal smear cytology was examined. Blood samples were taken by retro orbital technique on day 16 for evaluation of the reproductive hormones assay. Ovaries of the animals were removed for histological study. Group D (reversible group) were given 500 mg/kg of FSA extract for 15 days and further observed for 15 days for reversibility. The duration of days of proestrus in both treatment groups (250 and 500) mg/kg were significantly (P=0.004, P<0.001 respectively) prolonged and the diestrus phase was significantly shortened (P<0.001). Administration of 500 mg/kg FSA extract led to a decrease in the serum concentration of estrogen (P<0.001), progesterone (P=0.021), FSH (P=0.416) and LH (P=0.381) while serum prolactin concentration was significantly increased (P<0.001). The weight of ovaries were significantly (P=0.08) decreased and more degenerative follicles and congested blood vessel were observed in the treated group versus normal controls. After 15 days of treatment withdrawal, serum estrogen, progesterone, FSH and LH concentration were not significantly different (P≥0.192) in compare to the control group. The estrous cycles slowly returned to normal cycle after 10-15 days of withdrawal and no histopathological findings were noted in the ovarian tissues. FSA extract showed reversible anti-fertility effects by causing abnormalities in the estrous cycles regulation, alterations in serum concentration of reproductive hormones and histopathological changes in the ovarian tissues.